Aridity over a semiarid zone in northern China and responses to the East Asian summer monsoon. Issue 23 (5th December 2016) - Zhang, Hongli; Zhang, Qiang; Yue, Ping; Zhang, Liang; Liu, Qian; Qiao, Shaobo; Yan, Pengcheng
Abstract: In this study, the variability of the aridity over a semiarid zone in Northern China from 1961 to 2013 and its association with the northernmost margin of the East Asian summer monsoon (EASM) and its intensity were investigated using composite analysis, correlative analysis, and unrotated and rotated empirical orthogonal function analyses. The results indicate that a nonsignificant drying trend (0.03/10 years) occurs over the entire eastern semiarid zone, accompanied by a southward retreat in the northernmost margin of the EASM (0.24°/10 years), and that drying (0.11/10 years) and southward retreat (0.28°/10 years) are most obvious on the Loess Plateau. The response of the annual variation of aridity to changes in the northernmost margin of the EASM is also compared with its responses to changes in the intensity of the EASM; the results indicate that it is more related to the former, especially over the Loess Plateau. Furthermore, an abnormal aridity event is likely to occur over the Loess Plateau in a year when the EASM margin advances to its northernmost latitude abnormally ahead of time and retreats abnormally ahead of time compared to the mean state. Key Points: Semiarid climate in responses to the northernmost margin and intensity of the East Asian summer monsoon The response of aridity to northernmost margin is better than the intensity of the EASM, and this is most obvious on the Loess Plateau Abnormal aridity occurs if the EASM advances to its northernmost latitude early (38 pentad) and retreats early (45 pentad)